Astrocyte Heterogeneity in the Adult Central Nervous System - Miller, Sean J. (Frontiers in Cellular Neuroscience, 2018)
Astrocytes are the most abundant cell type in the central nervous system (CNS), providing critical roles in the overall maintenance and homeostasis. Over 100 years ago, Cajal first showed morphological depictions of different astrocyte populations. Surprisingly, to date astrocytes remain classified in two groups based on their morphological and neuroanatomical positioning. However, accumulating evidence over the past few years is showing that astrocytes are highly diverse throughout the CNS. Astrocyte heterogeneity is not surprisingly, as these cells interact with all other cells in the CNS. Like neurons, astrocytes may also have subpopulations that vary in their functionality. In this mini review, we will explore some of the recent evidence in the adult central nervous system of astrocyte diversity. First, we will review the very little literature on healthy adult astroglia heterogeneity, followed by the identification of different subpopulations in disease states and how this varies between human and mouse. Exploring this new area of neuroscience will hopefully provide researchers with a new perspective on astrocytes and their heterogeneity throughout the CNS.